Updated incidence of dry eye syndrome in Germany - Posa, A.; Sel, S.; Dietz, R.; Sander, R.; Bräuer, Lars; Paulsen, Friedrich (Klinische Monatsblätter für Augenheilkunde, 2014)
Dry eye is one of the most common eye surface disorders. Patients suffer in particular from annoying subjective symptoms that compromise quality of life. The aim of the study was to find out when patients consult ophthalmologists in Germany and what symptoms they present.170 patients treated at ophthalmological practices in Bavaria, Saxony and Saxony-Anhalt with dry eye were surveyed regarding their symptoms.The majority of those questioned were 40 years of age or older (88 %) (average: 60), female (59 %) and described a variety of subjective symptoms (65 %). More than five different concurrent symptoms were named. There is a recognisable increase in cases - by more than 3.5 times - at the age of forty (in women) and fifty (in men).We hope to contribute with the data obtained to a more complete understanding of this highly complex pathological process. A further aim is to facilitate recognition of this mostly chronic condition in its early stages when the symptoms are still poorly defined. The data on the German population obtained here should become part of a comparative analysis within the international context. Despite considerable scientific effort, dry eye remains a difficult challenge for both patients and attending physicians.
EVALuna2:4437